Challenges and Strategies in the Implementation of E-Government in Bandar Lampung City: A Comparative Study - Sa’adih, Sa’adih; Fahmi, Ade; Perdanaputra, Decky (JURNAL SOSIAL DAN HUMANIS SAINS, 2021)
This study explores the challenges and strategic approaches in the implementation of e-government in Bandar Lampung City through a comparative analysis of several local government departments. Utilizing a qualitative case study method, data were collected through interviews, document analysis, and observations across key institutions responsible for public digital services. The findings reveal that the adoption of e-government varies significantly across departments, with critical barriers including limited digital infrastructure, low digital literacy among civil servants, inconsistent standard operating procedures, and weak interdepartmental coordination. However, the study also identifies effective strategies such as leadership commitment, cross-sector collaboration, adaptive planning, and community engagement that contribute to more successful digital transformation. The research highlights the need for a holistic and context-sensitive approach to digital governance that addresses both technical and human resource dimensions. These insights can inform future efforts to strengthen the design and sustainability of e-government initiatives in mid-sized cities undergoing bureaucratic modernization.